Proceedings of the First International Congress on the Hellenic Diaspora from Antiquity to Modern Times (Montreal, 17-22.iv. 1988 ; Athens, 26-30.iv. 1988) : Volume 2: From 1453 to Modern Times - Fossey, John M. (Classical Studies - Book Archive pre-2000., 1991)
The print edition is available as a set of two volumes (9789050630603).